Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

f(x) = 2x3 + 5x^2 - 6x - 7
g(x) = 2x - 3
Find (f - g)(x).


Sagot :

9514 1404 393

Answer:

  (f-g)(x) = 2x^3 +5x^2 -8x -4

Step-by-step explanation:

  (f -g)(x) = f(x) -g(x)

  (f -g)(x) = (2x^3 +5x^2 -6x -7) -(2x -3) = 2x^3 +5x^2 -6x -7 -2x +3

  (f -g)(x) = 2x^3 +5x^2 -8x -4